Geomechanical characterization of potential roseneath shale gas, Cooper basin, Australia - Iqbal, O. (Asian Research Publishing Network, 2017)
Roseaneath and Murteree shale in Cooper basin, South Australia are proven seal, source as well as shale gas reservoir rock. Source rock characterization as a potential gas requires extensive understanding about the geomechanical properties for optimization of stimulation treatment and in order to avoid well bore instability and sand production during drilling and completion stages. Fifteen samples were selected from Moomba 191 well (depth 8473--8475 ft) drilled in Cooper Basin by DSD, Australia. The Triaxial compression and unconfined compression tests were performed on samples in order to find static geomechanical properties. The wireline logs like sonic and density were used to find dynamic mechanical properties. The calibrations were carried out between static and dynamic parameters in order to get reliable calibrated values. The 1-D Mechanical Earth Model (MEM) was developed based on elastic parameters (Young's modulus, Poison's ratio), failure parameters (Cohesion, internal friction angle, compressive strength and tensile strength), in-situ stresses, pore pressure and mud weight. The calibrated Young's modulus and Poison's ratio were ranging from 15 GPa to 30 GPa and 0.20 to 0.3 respectively. Brittleness analysis (BI) (ranges from 0.2-0.78) exhibited brittle and ductile layers within the whole shale interval. The Brittle index (BI), Young's modulus and poison's ratio on brittle layers were range from 0.4 to 0.78, greater than 25 GPa and < 0.3 respectively for brittle layers. Based on failure parameters, insitue stresses and mud weight three possible locations for wellbore breakouts, fractures, has been identified where special considerations are needed to select the mud weight in order to avoid the problems i.e. sand production, wellbore instability. The strongest depths for minimum wellbore stability have been identified that have also high BI (0.6 to 0.69) and can be potential target for stimulation. Based on results, it has been concluded that this Roseneath shale interval of Moomba 191 well have many critical zones based on limits of upper and lower safe mud weight window where extra care need to be taken. The normal stress regime exhibited that fractures orientation will be perpendicular to minimum horizontal stresses. © 2006-2017 Asian Research Publishing Network (ARPN).